2001
DOI: 10.1002/bit.1132
|View full text |Cite
|
Sign up to set email alerts
|

Replacing factor‐dependency with that for lysozyme: Affordable culture of IL‐6‐dependent hybridoma by transfecting artificial cell surface receptor

Abstract: Cytokines and growth factors are indispensable for the propagation and maintenance of factor-dependent mammalian cells. However, cytokines are often so expensive that the use of factor-dependent cells for industrial applications such as protein production is often not practical. Based on our previous design of a binary hen egg lysozyme (HEL)-specific receptor composed of portions of the anti-HEL antibody and the erythropoietin receptor, a new pair of chimeric receptors having the intracellular domain of gp130 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In addition, both types of chimeric receptors could be employed to specifically amplify gene-transduced cells in an antigendependent manner in pro-B cell line Ba/F3 (antigen-mediated genetically modified cell amplification, AMEGA) (Kawahara et al 2003). However, in the case of 7TD1 cells, we detected HEL-dependent cell growth only after drugresistance selection, and the possibility of direct HEL selection (AMEGA) was not pursued (Kawahara et al 2001a). Furthermore, in the previous study for 7TD1 cells, we tried only one combination of chimera (V H -gp130 and V L -gp130), while we also found that heterodimeric combination (V H -gp130 and V L -EpoR) exhibited the best properties for cell growth in Ba/F3 cells transfected with plasmids (Kawahara et al 2001b) or transduced with retroviral vectors (Kawahara et al 2003).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, both types of chimeric receptors could be employed to specifically amplify gene-transduced cells in an antigendependent manner in pro-B cell line Ba/F3 (antigen-mediated genetically modified cell amplification, AMEGA) (Kawahara et al 2003). However, in the case of 7TD1 cells, we detected HEL-dependent cell growth only after drugresistance selection, and the possibility of direct HEL selection (AMEGA) was not pursued (Kawahara et al 2001a). Furthermore, in the previous study for 7TD1 cells, we tried only one combination of chimera (V H -gp130 and V L -gp130), while we also found that heterodimeric combination (V H -gp130 and V L -EpoR) exhibited the best properties for cell growth in Ba/F3 cells transfected with plasmids (Kawahara et al 2001b) or transduced with retroviral vectors (Kawahara et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Since the IL-6 signaling was successfully mimicked by the combination of V H -gp130 (Hg) and V L -gp130 (Lg) chimeric receptor chains in our previous studies (Kawahara et al 2001a;Kawahara et al 2003;Kawahara et al 2001b), 7TD1 cells were retrovirally transduced with the vector encoding the Hg and Lg chimeras with a wild-type EpoR TM sequence (pMK-Hg-ILg-IG) to create 7TD/HgLg cells. The cells were washed to remove IL-6 and selected in the medium containing no additional factor, 1 lg/ml HEL or 2 ng/ml IL-6.…”
Section: Amega Detection By Flow Cytometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of ScFv-gp130 (ScFvg) was as described (Ueda et al, 2000;Kawahara et al, 2001aKawahara et al, ,b, 2004. A plasmid FLJ00153 encoding human EpoR was obtained from Kazusa DNA Research Institute.…”
Section: Vector Constructionmentioning
confidence: 99%
“…In the following experiment, the cytoplasmic domains of HE and LE chimeric receptors were replaced with that of gp130 to create Hg and Lg chimeric receptors, respectively. Co-expression of Hg and Lg or Hg and LE resulted in HEL-dependent cell growth in factordependent cell lines (11,12). Furthermore, when the enhanced green¯uorescent protein (EGFP) was employed as a model transgene and placed downstream of the LE gene and the internal ribosomal entry site (IRES), HEL induced speci®c ampli®cation of the cells with high expression level of EGFP (13).…”
Section: Introductionmentioning
confidence: 99%